Microbiota and inflammatory bowel disease - Jansson, Janet (Henry Stewart Talks, 2011)
Human gastrointestinal tract, The normal microbiota: development and contributing factors, Impact of disease on the human intestinal microbiota and vice versa, Fingerprinting of the gut microbiota, Crohn's disease: symptoms, complications, etiology, Evidence for microbial involvement in IBD, Dysbiosis, Genetics and IBD, Twin studies, Genomics vs. proteomics, Metaproteomics and metagenomics, Metabolite data